Coupled 142Nd-143Nd Isotopic Evidence for Hadean Mantle Dynamics - Bennett, Victoria; Brandon, Alan D; Nutman, Allen P (American Association for the Advancement of Science, 2015)
The oldest rocks - 3.85 billion years old - from southwest Greenland have coupled neodymium-142 excesses (from decay of now-extinct samarium-146; half-life, 103 million years) and neodymium-143 excesses (from decay of samarium-147; half-life, 106 billion